Sistem Pakar Diagnosa Error Sistem Pada “PT. Danaco Global Solusi – OXY System” Menggunakan Metode Certainty Factor Berbasis Web - Ginantra, Ni Luh Wiwik Sri Rahayu; Sandi, Victor Ari (SINTECH (Science and Information Technology) Journal, 2018)
In building a system can’t be separated from an error where for a company that works in Building a software this will be very dangerous if not quickly Handled, certainly beside with quickly also need to be handled accurately. Expert systems can be a solution where the expert system is capable of recording a person's ability to think or reason. Thought or reasoning of an expert will be used to diagnose from some of the symptoms that exist to conclude error with expert's specified weight while the belief to symptoms that are not certain will be determined by the user and determined using Certainty Factor method that can calculate the value of uncertainty so that error fixed can be concluded. The results of the implementation is 2 diagnosis with the highest level of confidence and the step to handling. Other results is the system accuracy by performing a comparison between the results of the diagnosis system to the actual event so that the accuracy is 91.667%